1995
DOI: 10.1161/01.cir.91.5.1320
|View full text |Cite
|
Sign up to set email alerts
|

Late Lumen Loss After Coronary Angioplasty Is Associated With the Activation Status of Circulating Phagocytes Before Treatment

Abstract: Background The purpose of this pilot study was to identify biological risk factors for restenosis after percutaneous transluminal coronary angioplasty (PTCA) to predict the long-term outcome of PTCA before treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(79 citation statements)
references
References 25 publications
1
76
2
Order By: Relevance
“…Most systemic pharmacological therapies have been unsuccessful in preventing arterial restenosis in humans, and the preliminary results of drug-eluting stents are remarkable in reducing in-stent restenosis. Nevertheless, LBPs offer a systemic therapy to a systemic process, 4,32 regardless of the procedure and the device(s) used. If effective in a clinical setting, it may be an easily adminis-tered, cost-effective modality that allows flexibility in choosing the type and number of stents to be deployed, may serve as an adjunct therapy in high-risk patients, and may even reduce the need for stenting altogether.…”
Section: Danenberg Et Al Liposomal Alendronate Inhibits In-stent Restmentioning
confidence: 99%
See 1 more Smart Citation
“…Most systemic pharmacological therapies have been unsuccessful in preventing arterial restenosis in humans, and the preliminary results of drug-eluting stents are remarkable in reducing in-stent restenosis. Nevertheless, LBPs offer a systemic therapy to a systemic process, 4,32 regardless of the procedure and the device(s) used. If effective in a clinical setting, it may be an easily adminis-tered, cost-effective modality that allows flexibility in choosing the type and number of stents to be deployed, may serve as an adjunct therapy in high-risk patients, and may even reduce the need for stenting altogether.…”
Section: Danenberg Et Al Liposomal Alendronate Inhibits In-stent Restmentioning
confidence: 99%
“…1,2 Macrophage content in atherectomy tissue and activation status of blood monocytes correlate with an increased rate of restenosis in humans. 3,4 We recently showed that transient macrophage depletion reduces experimental neointimal formation after balloon injury in rats and rabbits. 5 Stent deployment profoundly alters vascular repair, and the role of innate immunity in late restenosis is further stressed.…”
mentioning
confidence: 99%
“…Several studies have supported the critical role of inflammation in this process. There are some animal and human studies implicating pre-exiting inflammation in the development of restenosis (10)(11)(12). Current study excluded patients with infectious and active inflammatory diseases (rheumatoid arthritis, inflammatory bowel disease, etc).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Percutaneous transluminal coronary angioplasty (PTCA) with or without stent implantation is an established revascularization procedure; however, restenosis rates still range between 30-60% 6 and 15-30%, 7 respectively Preprocedural identification of low-and high-risk patients who might benefit from additional procedures 6,8 would be desirable. However, the predictors of early [7][8][9][10] and late complications [11][12][13][14][15] have a low predictive value, [15][16][17][18] are available only after procedures, 9,14 or are not easily applicable in clinical practice. 10,12,13 Inconsistent and weak correlation with early complications following PTCA was reported for female gender, extreme age, diabetes, multivessel disease, lesion characteristics, and hemostatic variables.…”
Section: Introductionmentioning
confidence: 99%